Efectividad del teatro de títeres en un programa de desarrollo rural. (1978)
A study was realized with the purpose to evaluate three different communication strategies in a health campaign. The campaign was directed to reach the participant of the "Oriente Antioqueño" Intcgrated Rural procct. The strategies used were: puppet theatre alone, puppet theatre + a lecture and puppet theatre + lecture + a promotional hand bill. The study had the following objcctivcs: I. To determine the effectiveness of the three strategies in promoting educational information related with the purity of the water for cmiisupt inn and health; and how to build a filter system to fuifill that need in the area. . To determine the ruralpeopie knowledge about the purpose and subject matter of the pampaign. To determine the rural people attitude, before and after the puppet theatre show. To determine the Ievci of comprehension of the campaign message divulgatcd with the strategies. To determine the relationships between level of knowledge. comprehension and the sex, age and education of the participants. The strategies were distributed at random among, six comniunit is in three different municipalities of the Integrated Rural Development Distric of Rionegro - Oriente Antioqueflo and the data was collected from the peasants, with three differents qucstionaircs, identified as participants in the program who attended the puppet theatre meetings. In the study four puppets ''guinol and a "hwnanettc type were used with which the piece entitled "Be carefull with impure water-How and why to purify the water" was shown. The piece had and cniot ive treatment in a atmosphere of hilarit and folkiife, emphasizing the establishment of a dialogue during the puppet-show. 633 In order to determine if the results obtained were by chance or by the effect of the treatments the following statistical tests were used: Differences of proportions. "t" test, Analysis of Variance and chi-square. The change of attitude was shown in graphic figures and percentages. The results indicate that the three strategies increased the peasants' knowledge significat ively under the study conditions. The comprehension of the message was indepetident of the variables sex, age, and level of education. In relation to the audience attitude toward the problem the data showed that there was a felt need for the filter system in the communities, in consequence, the campaign message contributed to enhance the attitudes of the peasants toward actions taken directed to solve the problem. The data also indicated that the puppet theatre was accepted by the peasants as a means to receive educational inforniation as well as a recreational show. As a result of the study it can he concluded that the puppet theatre is and efficient way to transfer technologies to the rural people independent of sex, age and education and as a way for increasing knowledge of the rural communities under anyone of the strategies utilized According to the researchers' observations it' could be said that the puppet theatre is an authentic mean for consciousness raising because it establishes a dialogue between the puppets and the audience, something that encompass within the humanistic conception of education.